Efektivitas Kombinasi Terapi Relaksasi Benson dan Murottal Surah Al-Kahfi terhadap Tekanan Darah pada Pasien Hipertensi di Desa Kedungdowo Kaliwungu Kudus - Putri Dina Kharisma Yana; Sukarmin Sukarmin; Fitriana Kartikasari (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Hypertension is a condition where arterial blood pressure is persistently above normal values. Hypertension management does not only rely on pharmacological therapy, but also requires a non-pharmacological approach as a complementary effort. One non-pharmacological intervention that can be used is Benson relaxation therapy and murottal Surah Al-Kahfi. Both therapies are believed to contribute to lowering blood pressure through the mechanism of reducing stress responses, increasing physiological relaxation, and achieving psychological calm. This study aims to test the effectiveness of the combination of Benson relaxation therapy and murottal Surah Al-Kahfi in lowering blood pressure in hypertensive patients. The study design used a quasi-experimental approach with a pretest-posttest approach and a control group. The study population was 40 people who participated in the prolanis program in Kedungdowo Village. Based on inclusion and exclusion criteria, a sample of 36 respondents was taken, divided into two groups: 18 people in the intervention group who received a combination of Benson relaxation therapy and murottal, and 18 people in the control group who were not given any intervention. The Wilcoxon signed-rank test results in the intervention group showed an effect of Benson relaxation therapy and recitation of Surah Al-Kahf in the elderly (p-value 0.004). The control group showed a p-value of 0.102. The Mann-Whitney test results showed a p-value of 0.044, indicating a difference in post-test blood pressure in those with hypertension in the control and intervention groups.